2018
DOI: 10.3390/tropicalmed3010003
|View full text |Cite
|
Sign up to set email alerts
|

Tick-, Flea-, and Louse-Borne Diseases of Public Health and Veterinary Significance in Nigeria

Abstract: Mosquito-borne diseases are common high-impact diseases in tropical and subtropical areas. However, other non-mosquito vector-borne pathogens (VBPs) may share their geographic distribution, seasonality, and clinical manifestations, thereby contributing their share to the morbidity and mortality caused by febrile illnesses in these regions. The purpose of this work was to collect and review existing information and identify knowledge gaps about tick, flea-, and louse-borne diseases of veterinary and public heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 128 publications
(238 reference statements)
0
11
0
1
Order By: Relevance
“…Several ticks have been implicated in transmission of EP to horses, including Rhipicephalus evertsi evertsi, Rhipicephalus decoloratus, Hyalomma impeltatum, Hyalomma. truncantum, Hyalomma dromederii, and Amblyomma variegatum (Onyiche et al 2019;Scoles and Ueti 2015), and some of these are found in Nigeria (Oguntomole et al 2018), though not on equids. However, horses are not the preferred host for some ticks identified, and their natural disease relationships are not well-known.…”
Section: Introductionmentioning
confidence: 98%
“…Several ticks have been implicated in transmission of EP to horses, including Rhipicephalus evertsi evertsi, Rhipicephalus decoloratus, Hyalomma impeltatum, Hyalomma. truncantum, Hyalomma dromederii, and Amblyomma variegatum (Onyiche et al 2019;Scoles and Ueti 2015), and some of these are found in Nigeria (Oguntomole et al 2018), though not on equids. However, horses are not the preferred host for some ticks identified, and their natural disease relationships are not well-known.…”
Section: Introductionmentioning
confidence: 98%
“…Since Nigeria acts as a major crossroads of animal transport in West Africa, and Nigeria and most neighboring countries are considered endemic for EP, the genetic characterization of circulating parasites in subclinical animals may shed light on the possible routes of parasite transmission in the area. Nigeria is also a habitat of several of the documented vectors species of EP [6,7], including Rhipicephalus evetsi which was the predominant species found on horses in Zaria city (Idoko Sunday Idoko, University of Abuja, unpublished data). Four of the five previously described T. equi 18S rRNA genotypes A, B, C and D were found in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…The predominant vectors of EP are wide-range tick species of the genera Amblyomma, Dermacentor, Haemaphysalis, Hyalomma and Rhipicephalus [6]. Four of these five genera have been documented in Nigeria [7]. Equine piroplasmosis, which is endemic in Nigeria, has, until now, been documented mostly in horses [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Indirect adverse consequences of tick infestation in cattle are linked to the conditions that are caused by the plethora of tick-borne pathogens (TBPs), including mostly protozoa and bacteria, but also helminths, viruses and fungi, some of which are of zoonotic importance [1][2][3][4] In spite of the enormous burden of ticks and TBPs on livestock farming, for many parts of SSA, even fundamental epidemiological information is lacking. Nigeria is a case in point; despite one of the largest cattle populations in the continent (of approximately 20 million heads) [5], contributing one third of national agricultural GDP and providing 36.5% of the total protein intake of Nigerians [6], substantial gaps affect the current understanding of the epidemiology of ticks and TBPs in the country [7], with knowledge of cattle-associated tick diversity and distribution being rather patchy [8][9][10][11][12] when not outdated [13][14][15][16]. Additionally, although approximately 90% of the country's cattle population is concentrated in the Northern region [6,17], most historical surveys were carried out in southern States [13,18].…”
Section: Introductionmentioning
confidence: 99%